Breast feeding Status of Infants Born in a Baby Friendly Hospital Up to 180 days of life - Das, Nanda Lal; Alam, Md Shafiul; Khan, Md Fazlul Kader; Islam, Khandaker Tarequl; Khan, Md Shahadat Hossain; Azam, Md Shaiful; Rana, Rubina Afroz; Afrooz, Farzana; Islam, Sajani; Sarker, Anwesa; Khatun, Sufia (Northern International Medical College Journal, 2023)
Background : Initiation of breast-feeding (BF) within 1 hour after birth has been associated with reduced neonatal mortality. Baby Friendly Hospital Initiative has profound effects on appropriate practice of BF and thus helps to reduce infant mortality and morbidity. Objective : This study was conducted in the Department of Gynae and Obstetrics and Department of Paediatrics of Shaheed Suhrawardy Medical College Hospital (ShMCH), Dhaka, to observe the rate of exclusive breast feeding and home-based compliance. Methodology : Hundred (100) term babies of normal birth weight irrespective of sex, born in ShSMCH by normal vaginal delivery (NVD) or caesarian section were included. Data was collected from the mother with a pretested questionnaire at the postnatal period, at 6th week, 14th week and 6th month (180 days) of age. Result : The mean age of studied newborn (100) was 20±19.5 hours. All the infants started breast feeding after birth and among them 56% initiated with in 1 hour. Difficulty in breast feeding was found in 36(36.0%) infants, which was resolved mostly (94%) by nurse. Exclusive breastfeeding (EBF) was found in 100% of infants during discharge from hospital. During 1st and 2nd follow up we found 95 (95.0%) and 89 (89.0%) infants respectively were exclusively breastfed. In 3rd follow up at completed 6th month (180 days) 78 (78.0%) infants were exclusively breast fed. In our study 5 (5%) and 6 (6%) infants received supplementary food in 1st follow up and in 2nd follow up respectively. In the last follow up the number were 11 (11%) and the total number was 22 (22%). Conclusion : Exclusive breast feeding up to completion of 6 months (180 days) was found in 78.0% of infants. Maternal and relative’s misperception of baby’s crying due to insufficient breast milk and joining to job outside home were the causes of introduction of formula milk in the 1st, 2nd and 3rd visit respectively. Northern International Medical College Journal Vol. 12 No.2 Jan 2021, Page 530-534